Long-read sequencing reveals HBV integration patterns and oncogenic impact on early-onset hepatocellular carcinoma - Wang, Yao; Yu, Dong; Mei, Yue; Fu, ZhiDa; Lin, Jian; Wu, Di; Yang, Yuan; Yan, Hongli (Genome Research, 2025)
Hepatitis B virus (HBV) integration is a key driver of hepatocellular carcinoma (HCC) occurrence and progression; however, its oncogenic mechanisms remain incompletely understood because of limitations in detection methods and sample availability. In this study, we employ Oxford Nanopore Technologies (ONT) whole-genome sequencing and full-length transcriptome sequencing to characterize HBV integration events at the genomic and transcriptomic levels, along with their regulatory effects on structural variations (SVs) and gene expression. Functional validation is performed using dual-luciferase assays and cell-based experiments. Our findings reveal that integrated HBV sequences form long concatemers, mediating inter- and intrachromosomal recombination in the human genome. Notably, integrated HBV enhancer I (HBV-Enh I) is detected in six of seven tumor tissues and is associated with aberrant gene expression. HBV integration induces oncogenic SVs, such as focal MYC amplification and NAV2 deletion, and directly modulates gene expression. Additionally, ectopic overexpression of MYOCD, driven by HBV-Enh I integration, promotes HCC cell migration and invasion. In summary, HBV integration acts as a major driver of large-scale genomic SVs and transcriptomic dysregulation, through either direct alterations in genome dosage or cis-regulatory mechanisms. HBV-Enh I is frequently integrated in HCC and might play a pivotal role in abnormal gene expression, highlighting its potential as a therapeutic target.